DAMPAK PENGGUNAAN GADGET PADA ANAK USIA DINI - Hikmaturrahmah, Hikmaturrahmah (Musawa: Journal for Gender Studies, 2018)
The 2003 National Education System Law which describes the time of children is 0-6 years of age) and some child education experts provide limitations of 0-8 years. At this time, Children who are in a time of curiosity are very helpful to read and use gadgets and some of the applications in them. With the development of information technology, children today are calling for far more "technology conscious" beyond the generations behind it. Indeed, on the one hand, there are several benefits for children who from the beginning have become acquainted with the gadget. At least since the beginning the child is familiar with technology. Here are summarized a number of gadget gadgets in children: Risk of electromagnetic radiation, reduced psychomotor abilities, difficulty adapting to lesson material. While Positive Impact: Facilitates communication, Increases knowledge, makes it easy to control children.